Investigating the Effect of Brand Equity on Rural Tourism Development with the Mediating Role of Word-of-Mouth Advertising. Case Study: Pristine Villages of Zanjan Province - AZIMI, Hossein (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
In recent years, due to the expansion of urban life, many people tend to travel to quiet and pristine environments. Therefore, the development of rural tourism can be one of the most important ways to generate income and economic development. In terms of purpose, this research is application-oriented and is descriptive-analytic in terms of method of work.  The statistical population of the study includes all tourists visiting the pristine villages of Zanjan province. Sampling method was available sample for 384 individuals. Data collection was based on a localized questionnaire. The validity of the questionnaire was confirmed by content and construct validity (KMO = 0.812) and its reliability was confirmed by Cronbach's alpha coefficient (0.903). Descriptive and inferential statistical methods were used for data analysis. SPSS and LISREL were used for descriptive and inferential analysis. The results of the study using the structural equation model indicate that there is a positive and significant relationship between brand equity and rural tourism development.